Analysis of the spatial and temporal sensitivities of key parameters in the SWAN model: An example using Chan-hom typhoon waves. (5th January 2020) - Xu, Yao; Zhang, Jicai; Xu, Yun; Ying, Wangmin; Wang, Ya Ping; Che, Zhumei; Zhu, Ye
Abstract: In this work, the spatial and temporal sensitivities of the significant wave height (SWH) to ten key parameters in the SWAN model under typhoon conditions are assessed through comprehensive observations at four buoy stations along the eastern coast of China. Experiments were conducted using wind forcing based on Typhoon Chan-hom, which made landfall at Zhujiajian island in 2015. Assessments included wind input and whitecapping, bottom friction, depth-induced wave breaking, and nonlinear quadruplet wave interactions parameterizations. The results show that in shallow water whose depth is less than the threshold depth, depth-induced wave breaking dominates the SWH, and the SWH is most sensitive to the parameter gamma (the ratio of maximum individual wave height to depth) of depth-induced wave breaking. However, beyond a certain threshold depth, the sensitivity of the SWH to depth-induced wave breaking begins to reduce. This threshold depth depends on sea states and ranges from 5 m to 30 m. In deep water, where the water depth is more than the threshold depth, SWH is primarily influenced by wind input and whitecapping. In general, the sensitivity is greater in coastal areas than in the open ocean. With regard to sea state, the higher the sea state, the deeper the threshold depth. The four different numerical procedures of four-wave interactions (so-called quadruplets) mainly affect the distribution of wave energy, not the SWH. In addition, the SWH is most sensitive to the drag coefficient, and bigger wave implies greater sensitivity. The study of spatial and temporal sensitivities of key parameters is of great significance for further application of the SWAN model and wave simulations, especially typhoon wave simulations. Highlights: In shallow water, depth-induced wave breaking dominates the significant wave height (SWH). In deep water whose depth is more than the threshold depth, SWH is primarily influenced by wind input and whitecapping. This threshold depth depends on sea states and ranges from 5 m to 30 m. The higher the sea state, the deeper the threshold depth.